The nurse teacher's pedagogical cooperation with students, the clinical learning environment and supervision in clinical practicum: a European cross-sectional study of graduating nursing students. - Strandell-Laine, Camilla; Salminen, Leena; Blöndal, Katrín; Fuster, Pilar; Hourican, Susan; Koskinen, Sanna; Leino-Kilpi, Helena; Löyttyniemi, Eliisa; Stubner, Juliane; Truš, Marija; Suikkala, Arja (BMC Medical Education, 2022)
Background: A supportive clinical practicum experience may enhance the successful transition and socialization to working life of graduating nursing students. Nurse teachers have the main responsibility of supporting and guiding nursing students with their pedagogical expertise during the students' clinical practicum. Thus, the clinical role of nurse teachers is seen as an essential part of a high-quality clinical practicum. Nursing students appreciate the nurse teacher's cooperation with students, but it is often reported to be unattainable. The aim of this study was to explore and compare graduating nursing students' experiences of the nurse teacher's pedagogical cooperation with students, the clinical learning environment and supervision in their final clinical practicum, and to analyze factors associated with these experiences in six European countries. Methods: A cross-sectional comparative international survey design was used. The modified Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T) Scale, with a new subscale measuring the nurse teacher's pedagogical cooperation with students, was used. A convenience sample of graduating nursing students in Finland, Germany, Iceland, Ireland, Lithuania and Spain completed the online survey in 2018-2019. The data were analyzed using a Chi-Square test, Pearson's correlation coefficients, and linear models. Results: A total of 1796 (response rate 49%) nursing students completed the survey. Overall, students had positive experiences of the nurse teacher's pedagogical cooperation, the clinical learning environment and supervision in their final clinical practicum. Students in Spain had the most positive experiences. Educational background factors appeared to be associated with the students' experiences of the nurse teacher's pedagogical cooperation with students, the clinical learning environment and supervision. The relationships between the subscale Nurse teacher's pedagogical cooperation with students and the Clinical Learning Environment and ...